Mnemonic as a Strategy in Enhancing the Memory of Students of Universiti Sains Malaysia - Abu Bakar, Khairul; Omar, Mohamad Yusuf; Ishak, Muhammad Azim; Harun, Nur Alia Asyura; Yasuni, Nurjannah (2017)
Mnemonics is a method to help memory store information or information that has been learned. Maizan (2017: 310) states that mnemonic techniques are helpful in remembering many complex and complex facts and increasing memory input, reducing stress and helping widen the memory scope in maximum. The highlight of the previous study shows that mnemonics are proven to be one of the effective methods and able to help individuals remember something in long-term memory regardless of age (Thomson 1987, Mastropieri 1991, Solso 1995). Among the research methodologies used in this study were written tests, demographic data collection, observation and data analysis. In this study, the organized mnemonic strategy is divided into two techniques namely the acronym for the Arts Flow subject, and the acrostic techniques for the Science stream subject. The findings show that this study can not reject the 'Zero' hypothesis because the value of 'P' obtained is greater than 0.05 which is 0.47, 0.32, 0.90, 0.09, and 0.10. This shows that there is no group effect on mnemonic test scores according to Literary and Science Flow. The proof is that participants will not be more aware of the content of the lesson with effective mnemonic techniques regardless of the background of the participants either from the Literary Flow and the Science Flow. In addition, the participants of the Science and Literature Flow tested will not be easier to remember mnemonic learning in whole or in part, when they often remember it for a long time. Furthermore, participants will not be more likely to remember the mnemonic of Literature than Science mnemonics in mastermnemonic techniques within the given time period. At the same time, this study shows the highest mean value for mnemonic Literary Flow is 96.68 per cent compared to 96.38 per cent for the highest mean flow of Science. Whereas the highest median mnemonics of Literary Flow and Science Flow are equal to 100 percent. The standard deviation shows 11.27 per cent for Literary Mnemonics and 7.76 per cent for Science Mnemonics. The results of the discussion show that there are factors that can be taken into account in determining mnemonic remedial errors such as mnemonic, social background and nutritional factors.